Comparison of non-volatile umami components in chicken soup and chicken enzymatic hydrolysate. (December 2017) - Kong, Yan; Yang, Xiao; Ding, Qi; Zhang, Yu-Yu; Sun, Bao-Guo; Chen, Hai-Tao; Sun, Ying
Abstract: Umami taste is an important part to the taste of chicken. To isolate and identify non-volatile umami compounds, fractions from chicken soup and hydrolysate were prepared and analyzed. Amino acids were analyzed by amino acid analyzer. Organic acids and nucleotides were determined by ultra-performance liquid chromatography. Separation procedures utilizing ultrafiltration, Sephadex G-15 and reversed-phase high-performance liquid chromatography were used to isolate umami taste peptides. Combined with sensory evaluation and LC-Q-TOF-MS, the amino acid sequences of 12 oligopeptides were determined. The amount of taste compounds was higher in chicken enzymatic hydrolysate than that of chicken soup. Eight oligopeptides from chicken enzymatic hydrolysate were identified, including Ala-Asp, Ala-Met, His-Ser, Val-Glu, Ala-Glu, Asp-Ala-Gly, Glu-Asp and Ala-Glu-Ala. Four oligopeptides from chicken soup were identified, including Val-Thr, Ala-His, Ala-Phe and Thr-Glu. Graphical abstract: Highlights: Twelve oligopeptides were isolated and identified in chicken soup and chicken enzymatic hydrolysate. AD, VE, AE, DAG, ED, AEA, AH, TE showed umami taste. The taste compounds in chicken soup were evaluated differently from those in chicken enzymatic hydrolysate.